The Gastroprotective Effects of Anisomeles indica against Ethanol-Induced Gastric Ulcer through the Induction of IκB-α and the Inhibition of NF-κB Expression - Chen, Yu-Ru; Lien, Hsiu-Man; Tsai, Fuu-Jen; Liao, Jiunn-Wang; Chen, Yng-Tay (Nutrients, 2024)
Anisomeles indica (L.) Kuntze is a traditional herb with multiple medicinal properties and with potential for preventing or treating various diseases. Acteoside, one of the active ingredients in A. indica, is prepared into commercially available products of A. indica HP813 powder. In this study, the gastroprotective effects of A. indica HP813 powder were evaluated. Wistar rats were treated with A. indica HP813 powder at doses of 0, 207.5, 415, and 830 mg/kg body weight for 28 days. Then, gastric ulcers were induced by the oral administration of 70% ethanol (10 mL/kg body weight) on day 28. The rats were sacrificed at the end of the trial, and stomach tissues were collected. These stomach tissues were then used for macroscopic, microscopic, and immunohistochemical analyses. The results indicated that the area of gastric ulcer was 48.61%, 35.30%, and 27.16% in the ethanol-induced group, 415 mg/kg A. indica HP813 powder group, and 830 mg/kg A. indica HP813 powder group, respectively. In addition, the lesion scores were 2.9, 2.4, and 2.3 in the ethanol-induced group, 415 mg/kg A. indica HP813 powder group, and 830 mg/kg A. indica HP813 powder group, respectively. The immunochemical staining of the gastric tissue revealed that A. indica HP813 powder reduced the expressions of TNF-α and NF-κB proteins in the gastric tissue, which had been induced by ethanol. Finally, A. indica HP813 powder protected the gastric ulcer from ethanol damage through IκB-α induction. The present results demonstrated that A. indica HP813 powder has protective effects against ethanol-induced gastric ulcer.